TANTANGAN PENDIDIKAN TEKNOLOGI INFORMASI DI KOTA BANDUNG: MENGHAMBAT TERWUJUDNYA SMART CITY DAN SMART PEOPLE - Shakila Adzira Putri Prasetyo; Nazwa Nafisha Januariska; Nabil Khairul Akmal; Ivan Darmawan (Triwikrama: Jurnal Ilmu Sosial, 2024)
A smart city is a digital transformation concept that aims to improve the efficiency of public services and the quality of life of the community through the use of technology. The application of this concept in the city of Bandung has begun to create a smarter city. The success of smart city implementation is not only determined by technological advances but also by the ability of society to adopt and use it effectively, thus reflecting the importance of the smart people concept. Smart people in this case refer to people who have high digital literacy, so they are able to contribute to supporting the success of digital transformation. Information technology education plays an important role in this, but there are various challenges in information technology education that can hinder the achievement of these two concepts. This article aims to identify challenges and provide recommendations for solutions to overcome these challenges so that it is hoped that it can help the City of Bandung overcome existing challenges and optimise the potential of the smart city and smart people concept in improving the quality of life of the community.